A modeling approach to estimate the 137Cs discharge in rivers from immediately after the Fukushima accident until 2017. (November 2019) - Sakuma, Kazuyuki; Nakanishi, Takahiro; Yoshimura, Kazuya; Kurikami, Hiroshi; Nanba, Kenji; Zheleznyak, Mark
Abstract: We developed a simple model to evaluate and predict the 137 Cs discharge from catchments using a tank model and the L-Q equation. Using this model, the 137 Cs discharge and discharge ratio from the Abukuma River and 13 other rivers in the Fukushima coastal region were estimated from immediately after the Fukushima accident up to 2017. The 137 Cs discharge (and discharge ratio to the deposition inventory in the catchment) of the Abukuma River and 13 other rivers in the Fukushima coastal region during the initial six months after the accident were estimated to be 18 TBq (3.1%) and 11 TBq (0.79%), respectively. These values of 137 Cs discharge ratio were 1–2 orders of magnitude higher than those observed after June 2011 in previous studies (Ueda et al., 2013; Tsuji et al., 2016; Iwagami et al., 2017a), indicating that the initial 137 Cs discharge from the catchments through the rivers was significant. The simulated initial 137 Cs discharge rates for the initial six months after the Fukushima accident were about 9–30 times larger in each catchment than those after that point until 2017, though initial 137 Cs concentration in river water was derived from an extrapolation of data based on a two exponentially decreasing fitting. However, it was found that the impact on the ocean from the initial 137 Cs discharge through the rivers can be limited because the 137 Cs discharge from the Abukuma River and the 13 other rivers in the Fukushima coastal region (29 TBq) was two orders of magnitude smaller than the direct release from Fukushima Dai-ichi Nuclear Power Plant (FDNPP) into the ocean (3.5 PBq) and from atmospheric deposition into the ocean (7.6 PBq) (Kobayashi et al., 2013). This model is expected to be useful to evaluate and predict 137 Cs discharge from catchments in future water management and in the estimation of 137 Cs discharge into reservoirs and the ocean. Highlights: A simple model was created to predict the radiocesium discharge from catchments. We estimated the 137 Cs discharge from catchments in the first six months after the Fukushima accident. Abukuma River had a 137 Cs discharge level of 18 TBq and 13 other rivers in the coastal region were at 11 TBq. The 137 Cs discharge rates during the initial six months was about 9–30 times larger than the period after that point. However the impact of the initial 137 Cs discharge through the rivers on the initial release into the ocean can be limited.